The Number of Bleaching Sessions Influences Pulp Tissue Damage in Rat Teeth - Cintra, Luciano Tavares Angelo [UNESP]; Benetti, Francine; da Silva Facundo, Aguinaldo Cândido; Ferreira, Luciana Louzada; Gomes Filho, João Eduardo [UNESP]; Ervolino, Edilson [UNESP]; Rahal, Vanessa; Briso, André Luiz Fraga [UNESP] (Elsevier, 2013)
Introduction: Hydrogen peroxide tooth bleaching is claimed to cause alterations in dental tissue structures. This study investigated the influence of the number of bleaching sessions on pulp tissue in rats. Methods: Male Wistar rats were studied in 5 groups (groups 1S-5S) of 10 each, which differed by the number (1-5) of bleaching sessions. In each session, the animals were anesthetized, and 35% hydrogen peroxide gel was applied to 3 upper right molars. Two days after the experimental period, the animals were killed, and their jaws were processed for light microscope evaluation. Pulp tissue reactions were scored as follows: 1, no or few inflammatory cells and no reaction; 2, <25 cells and a mild reaction; 3, between 25 and 125 cells and a moderate reaction; and 4, 125 or more cells and a severe reaction. Results from each experimental group were compared between groups and within groups to the corresponding unbleached upper left molars and analyzed for significant differences using the Kruskal-Wallis test (P < .05). Results: All tissue sections showed significant bleaching-induced changes in the dental pulp. After 1 bleaching session, necrotic tissue in the pulp horns and underlying inflammatory changes were observed. The extent and intensity of these changes increased with the number of bleaching sessions. After 5 sessions, the changes included necrotic areas in the pulp tissue involving the second third of the radicular pulp and intense inflammation in the apical third. Conclusions: The number of bleaching sessions directly influenced the extent of pulp damage. © 2013 American Association of Endodontists.
Keywords: Hydrogen peroxide; pulp reaction; tooth bleaching